2022
DOI: 10.1007/s43154-022-00077-6
|View full text |Cite
|
Sign up to set email alerts
|

Robotics and Autonomous Systems for Net Zero Agriculture

Abstract: Purpose of Review The paper discusses how robotics and autonomous systems (RAS) are being deployed to decarbonise agricultural production. The climate emergency cannot be ameliorated without dramatic reductions in greenhouse gas emissions across the agri-food sector. This review outlines the transformational role for robotics in the agri-food system and considers where research and focus might be prioritised. Recent Findings Agri-robotic systems pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…This behavior would significantly affect greenhouse agriculture in southeastern Spain, which makes intensive use of soil (Rufí‐Salís et al, 2020; Valera‐Martínez et al, 2014). In the future, the combined implementation of other production techniques that are currently experimental, such as digital twins or robotization, could further increase production costs and drastically decrease the economic profitability of the activity (Ariesen‐Verschuur et al, 2022; MAPA & Cajamar, 2022; Pearson et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior would significantly affect greenhouse agriculture in southeastern Spain, which makes intensive use of soil (Rufí‐Salís et al, 2020; Valera‐Martínez et al, 2014). In the future, the combined implementation of other production techniques that are currently experimental, such as digital twins or robotization, could further increase production costs and drastically decrease the economic profitability of the activity (Ariesen‐Verschuur et al, 2022; MAPA & Cajamar, 2022; Pearson et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, they demand the implementation of new production infrastructures, with the consequent expansion of the environmental footprint. This Cajamar, 2022;Pearson et al, 2022). et al, 2020).…”
Section: Statistical Treatmentmentioning
confidence: 93%
“…fertilizers and pesticides) [54,[64][65][66]. For example, annual soil tillage is one of the most energy-intensive activities on farms [54]; previous studies have shown that moving to no-till systems can halve on-farm energy inputs [62]. However, the impact of no-till on GHG emissions would vary by region, and no-till practices would lead to greater fertilizer and pesticide expenditures [67].…”
Section: Energy Efficiency and Conservation Agriculturementioning
confidence: 99%
“…Electrification can also improve the energy efficiency of on-farm energy use [27]. Fossil fuel-powered conventional tractors can be replaced by smaller and lighter electric machines, opening new avenues for the implementation of precision robotics and automation technologies [27,62]. Digitalization of agriculture with sensors, robots, and artificial intelligence can increase resource efficiency and reduce the need for energy and inputs (e.g.…”
Section: Energy Efficiency and Conservation Agriculturementioning
confidence: 99%
See 1 more Smart Citation